The relationship between product quality and transaction costs with vertical coordination in DOC [Qualified Designation of Origin] Rioja winegrape industry - Fernández-Olmos, M.; Rosell Martínez, J.; Espitia-Escuer, M.A. (Spanish Journal of Agricultural Research, 2009)
This paper analyzes the relationship between product quality and governance mode choice (market mode, hybrid mode or vertical integration) using the results of a survey of 187 qualified appellation of origin (DOC) Rioja wineries. By estimating a generalized ordered logit, it is concluded that wineries that produce high-quality wines are more likely to vertically integrate than are wineries that produce low-quality wines. Consistent with transaction cost economics, evidence is found that asset specificity and uncertainty are important determinants of vertical integration. Finally, the size of the winery is also an important factor that affects governance mode choice in viticulture.